Estimation Of Left Ventricular Ejection Fraction Using Mitral Annular Displacement Derived By Speckle Tracking Echocardiography In Patients With Different Heart Diseases - Kadhim, .Mohammed Ameen; AL- Marayati, .Amal N.; Haji, Ghazi F. (AL-Kindy College Medical Journal, 2015)
Background: Speckle tracking echocardiography (STE)-derived mitral annular displacement (MAD) utilizes the speckle tracking technique to measure strain vectors, which provides accurate estimates of left ventricular ejection fraction (LVEF).Objectives: To validate the accuracy of mitral annular displacement (MAD), assessed by Speckle Tracking Echocardiography (STE), as a surrogate for determination of left ventricular systolic function in comparison to 2-Dimensions Simpson method in patients with different heart diseases.Methods : This cross-sectional study included patients who referred to outpatient department of Ibn Albitar Center for Cardiac Surgery, Baghdad, Iraq, between October 2012 and April 2013. STE continuously tracked annular motion throughout the cardiac cycle in the apical 4- and 2-chamber views. LVEF for each patient was measured by both Simpson method and STE-derived MAD.Results: This study included 100 patients, of them (35%) had ischemic heart disease (IHD), (10%) had dilated cardiomyopathy (DCM), (10%) had valvular heart disease (VHD), (25%) had normal echocardiography, and (20%) had hypertensive heart disease (HHD).There was significant correlation between EF % (derived by MAD) and EF % (derived by Simpson method) in patients with different heart diseases. This correlation was good in normal subjects (r=0.673), and those with IHD(r=0.896), DCM (r=0.724) and VHD (r=0.935), while in HHD it was moderately correlated (r=0.455). There was slight under-estimation of LVEF derived by MAD (a mean value of difference 0.846 %; p =0.022). In subgroup analysis, this difference was seen only in patients with HHD (a mean value of difference 3.145 %; p